Efficacy of baclofen in combination with intensive rehabilitation in spastic cerebral palsy- a randomized clinical trial (Journal of Dhaka Medical College, 2015)
Objective: To find out the combined efficacy of baclofen and intensive rehabilitation in the treatment of spastic cerebral palsy. Methods: This randomized clinical trial was conducted over 60 patients in Dhaka Medical College Hospital, Dhaka, between January and December 2011. The patient satisfying the inclusion and exclusion criteria was randomly enrolled into two groups; Group A (case) included 30 patients received only intensive rehabilitation and Group B (control) included 30 patients who received baclofen orally two times daily according to the body weight regularly in combination with intensive rehabilitation 1 hour daily five times a week for 24 weeks. All patients were followed up at 4 weeks interval and were evaluated for a total of 24 weeks. Results: Combination of baclofen and intensive rehabilitation has superior efficacy in reducing tone in spastic cerebral palsy over only rehabilitation measured by using Modified Ashworth scale (p